Kandughna Gana Varti in Vulvo Vaginalcandidiasis - A Case Series - Simi Raj K K; Maya Balakrishnan; Giby Thomas (International Journal of Ayurveda and Pharma Research, 2022)
Vulvovaginal candidiasis is an infection caused by yeast like micro organisms called candida albicans. It is the second most common cause of vaginitis affecting women of reproductive age group. It is most distressing and irritating to women, hampers their day to day life and makes them irritable, depressed, anxious and disturbs their interpersonal relationships including marital life. In vulvovaginal candidiasis patients complain of vaginal discharge with intense vulvovaginal pruritus. The pruritus is out of proportion to the discharge. The symptoms of vulvovaginal candidiasis appear similar to the symptoms of Slaishmiki yoni vyapath mentioned in Ayurvedic classics. It is due to the vitiation of Kapha caused by usage of Abishyandi aharas and has symptoms like Pichila yonisrava, Kandu, Alpa vedhana or Avedhana in Yoni. Topical treatments have great importance in the treatment of several gynecological conditions (Yoni vyapaths). Yoni varti or vaginal pessary is used to cleanse the vaginal walls and make the local environment more healthy. It acts directly on the vaginal mucosa and enables easier and target specific action. They are also hygroscopic in property and act in accordance with the drugs they contain. Kandughna gana varti have Tiktha, Kashaya rasa, Laghu, Ruksha guna, Krimighna, Kandughna and Kaphaghna properties and all the ingredients have potent antifungal action also. This facilitates faster absorption of drugs through vaginal mucosa and relieves the symptoms more quickly. A pilot study was conducted in 5 cases to assess the effect of Kandughna gana varti in vulvovaginal candidiasis. It was found to be effective in vaginal discharge and vulvovaginal pruritus.